Cultural studies in Portugal: The present scenario - Sampaio, S. (Current Issues in European Cultural Studies, 2011)
In this paper I discuss the situation of cultural studies in Portugal by looking into its presence in Portuguese universities and research centres, especially through their master and doctoral programmes. My results suggest that cultural studies is experiencing a fast academic expansion. Yet, the name ‘cultural studies’ continues to cause unease in some academic quarters (namely, in literary studies) and there is ambiguity regarding what is meant by it. My results also suggest that the cur- rent expansion of cultural studies in the academia is entangled with top-down institutional changes, closely related to the Bologna process and the growing importance of the cultural industries, as part of a more general shift to the ‘new economy’.